2019
DOI: 10.5038/1944-0472.11.4.1695
|View full text |Cite
|
Sign up to set email alerts
|

Intervening in and Preventing Somali-American Radicalization with Counter Narratives: Testing the Breaking the ISIS Brand Counter Narrative Videos in American Somali Focus Group Settings

Abstract: Research has highlighted identity-related challenges within the Somali-American community, as many of them belong to the pool of firstgeneration immigrants and have in many cases failed to integrate into mainstream society. Vulnerabilities also become apparent as many

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The surveyed practitioners (Study 2) also reported positive changes in youngsters after program participation in terms of improvement of their social skills, but no change regarding the justification of violence. Regarding the counternarrative programs in general, according to Hassan, Brouillette‐Alarie, Ousman, Kilinc, et al (2021), the few existing evaluations are quite positive: those exposed to messages of peace and tolerance were more likely to become civically engaged (Aldrich, 2014), and those exposed to a counternarrative targeting ISIS propaganda expressed a negative evaluation of the organization (Speckhard, Shajkovci, & Ahmed, 2018). However, we cannot affirm that this negative evaluation led to a decrease in the individuals' radical intentions as this was not assessed in the mentioned evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…The surveyed practitioners (Study 2) also reported positive changes in youngsters after program participation in terms of improvement of their social skills, but no change regarding the justification of violence. Regarding the counternarrative programs in general, according to Hassan, Brouillette‐Alarie, Ousman, Kilinc, et al (2021), the few existing evaluations are quite positive: those exposed to messages of peace and tolerance were more likely to become civically engaged (Aldrich, 2014), and those exposed to a counternarrative targeting ISIS propaganda expressed a negative evaluation of the organization (Speckhard, Shajkovci, & Ahmed, 2018). However, we cannot affirm that this negative evaluation led to a decrease in the individuals' radical intentions as this was not assessed in the mentioned evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…This article details the utility of counter narratives in disrupting ISIS's online recruitment and indoctrination efforts and in eliciting engagement from users most susceptible to online exposure to terrorist propaganda, echoing previous ICSVE research [17][18][19][20][21]. This latest development in counter narrative strategy, hyper-targeting Facebook profiles with the generous assistance of Facebook, demonstrates that ICSVE's counter narratives are even more effective in engaging members of the target audience than the general population, which gives validity to their efficacy as powerful counter messaging tools and ICSVE's methods in distributing them online.…”
Section: Discussionmentioning
confidence: 78%
“…The purpose of these campaigns was to continue to raise awareness and challenge narratives of extremist groups such as ISIS, but to do so in hyper-focused samples judged by prior analysis as vulnerable due to prior exposure to terrorist recruiting content. Previously initiated ICSVE Facebook campaigns focused on raising general awareness about groups such as ISIS or included smaller datasets of ISIS endorsers or sympathizers [17][18][19][20][21]. In contrast, this research encompassed one of the largest data sets by ICSVE that directly targeted users who were likely to have been exposed to propaganda, such as that distributed by those who sympathized or referenced a direct support for militant jihadi, including ISIS and al Shabaab, violent extremist groups on Facebook.…”
Section: Discussionmentioning
confidence: 99%